2016
DOI: 10.1021/acsnano.6b06061
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Delivery of Functionalized Gold Nanoparticles Target and Activate Dendritic Cells in a 3D Lung Cellular Model

Abstract: Nanocarrier design combined with pulmonary drug delivery holds great promise for the treatment of respiratory tract disorders. In particular, targeting of dendritic cells that are key immune cells to enhance or suppress an immune response in the lung is a promising approach for the treatment of allergic diseases. Fluorescently encoded poly(vinyl alcohol) (PVA)-coated gold nanoparticles, functionalized with either negative (−COO − ) or positive (−NH 3 + ) surface charges, were functionalized with a DC-SIGN anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Positively charged NPs enhance the electrostatic attraction between NPs and negatively charged cell membrane, leading to the increased surface endocytosis (or phagocytosis) [56]. Hence, cationic NPs showed higher uptake in macrophage and DCs [57,58]. Hu et al demonstrated that positively charged Fe 2 O 3 NPs enhanced the cross-presentation ability of DCs, while negatively charged Fe 2 O 3 NPs were associated with rapid autophagy [59].…”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%
“…Positively charged NPs enhance the electrostatic attraction between NPs and negatively charged cell membrane, leading to the increased surface endocytosis (or phagocytosis) [56]. Hence, cationic NPs showed higher uptake in macrophage and DCs [57,58]. Hu et al demonstrated that positively charged Fe 2 O 3 NPs enhanced the cross-presentation ability of DCs, while negatively charged Fe 2 O 3 NPs were associated with rapid autophagy [59].…”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%
“…It has been previously reported that surface-exposed dye molecules, such as non-shielded ATTO590,i nterfere with cellular uptake.T his makes shielded NPs favorable candidates,s ince the polymer used provides protection from the dye while the fluorescence remains uncompromised. [7] AuNPs were selected as model NPs not only for their well-established synthetic procedure but also because they did not show any adverse effects in previous in vitro [10] or in vivo [11] studies. Moreover,t he fluorescent dye allows the detection and quantification by flow cytometry,f luorescence spectroscopy, and imaging techniques,hence allowing the direct tracking of the fate of NPs.…”
mentioning
confidence: 99%
“…To study this specifically in DCs, Fytianos et al coated AuNPs with PVA and functionalized them with either COO − or NH 3 + . The results showed that AuNP‐PVA and NH 3 + induced better uptake (5% vs 30%) efficiency than COO − . Interestingly, uptake of the AuNP‐PVA and using DC‐SIGN as the targeting molecule to DCs was independent of charge .…”
Section: Surface Charge Impacts Internalization By Dendritic Cellsmentioning
confidence: 97%